Mentor teachers’ feedback role in improving the training of Grades 1-3 student teachers in South Africa - Anna Johanna Hugo (African Journal of Teacher Education, 2018)
Mentor teachers play a vital role in the pre-service training of teachers.  The role of mentor teachers assumes even more significance when the training is done at a distance education institution.  It is impossible for lecturers and university representatives to reach every teacher student during the weeks of teaching practice done at schools in a big country like South Africa.  The feedback obtained from the mentor teachers is thus important to train student teachers when they present their lessons during weeks of teaching practice at schools.  But the feedback from mentor teachers can also be used for the future training of student teachers.  Mentor teachers should, however, also be informed about their role as mentors for student teachers.  In this article the way feedback of mentor teachers could be used to improve the quality of the lessons of student teachers when offering language lessons in Grades 1 – 3, is discussed.